Double Pulse LIBS of Titanium-Based PVD-Coatings with Submicron Resolution. (6th March 2016) - Ermalitskaia, K.; Voropay, E.
Abstract : The possibility for double pulse LIBS in the process of a direct layer-by-layer analysis of the titanium-based PVD-coatings on polished flat blank samples of steel and silicon and also of the TiAlN/TiN-coating on a milling cutter is considered. A method is proposed to control thickness of the radiation evaporated layer by defocusing the laser beam with respect to the surface, making it possible to attain the depth resolution of 0.1  μ m. The Ti and Ti-Zr-coatings produced using the ion-assisted condensation method and subjected to streams of the nitrogen plasma in a magnetic-plasma compressor are studied.